Pengetahuan Guru Pendidikan Jasmani Tentang Pola Gerak Dominan Senam Terhadap Partisipasi Siswa pada Materi Senam Lantai - Martini, Tri; Winarni, Sri; Mulyaningsih, Farida (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to determine the level of knowledge of junior high school physical education teachers in West Java regarding dominant movement patterns (PGD) in gymnastics and the level of student participation in learning with floor exercise material. The research was conducted through a quantitative descriptive approach. Participants in this research consisted of 45 physical education teachers who were respondents from 15 schools throughout West Java and 287 students of SMPN 10 Cirebon City in grades VII and VIII. The instrument used was a questionnaire. The technical data analysis used is descriptive quantitative, with the results of assessments of all teachers and students carried out using the same tool. The results are divided into five categories: high, high, medium, low, and low. Based on the research results, the level of knowledge of Physical Education Teachers regarding Dominant Movement Patterns (PGD) in gymnastics is high, with a total of 22 teachers (42.3%). In comparison, the lowest are teachers with very low knowledge, with four teachers (7.7%). For student participation in the floor exercise material, most students had low participation, with a total of 136 students (47.4%). In comparison, 60 students (20.9%) were students with the highest involvement, and the fewest were students with very low participation, with a total of 19 students (6.6%). Keywords: Teacher knowledge, dominant movement patterns in gymnastics, floor exercise, student participation